KUALE Surprise and Balloon / Nur Amelia Hayani Muhammad Faiz - Muhammad Faiz, Nur Amelia Hayani (2020)
In this case study, we need to find and make some research to know how the business was established, how the founders manage the shop and the business, what the strategies that founders use to attract the customers to repeat order and also how the founders make the business well known. So, in this report we will know all the secret, the strategies and opportunity that these founders used in their business. In addition, when I do the research and studying about this business, I can get and find out more about this business such as about the background of founders and business, the type of this business, about the capital, profitability, products that they produced, the challenge and how they manage the business. So, if one day I want to open my own business, I can follow the step or maybe learn from the mistakes that founders once made while developing their business. Other than that, the business field that the owner in involved in is quite limited in expanding the market, it is because the competition is quite large and the potential to get customers is quite low because most of them think it can be made by ourself. So, for sure the founders need to be creative, innovate and have the strategy to attract the customers and expand the market.